2010
DOI: 10.1021/jf1002446
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Select Edible Oilseed Proteins

Abstract: Borate saline buffer (0.1 M, pH 8.45) solubilized proteins from almond, Brazil nut, cashew nut, hazelnut, macadamia, pine nut, pistachio, Spanish peanut, Virginia peanut, and soybean seeds were prepared from the corresponding defatted flour. The yield was in the range from 10.6% (macadamia) to 27.4% (almond). The protein content, on a dry weight basis, of the lyophilized preparations ranged from 69.23% (pine nut) to 94.80% (soybean). Isolated proteins from Brazil nut had the lightest and hazelnut the darkest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 66 publications
4
39
1
5
Order By: Relevance
“…The colour a and b values, respectively are indicative of redness and yellowness. These values depend on the combination of several components including quantity of total phenolics, colouring pigments and minerals and type of phenolic compounds (Sharma et al 2010). The a values (redness) of DHC and DHCP (5.34 and 5.28) were not significantly different (p>0.05).…”
Section: Colourmentioning
confidence: 89%
See 4 more Smart Citations
“…The colour a and b values, respectively are indicative of redness and yellowness. These values depend on the combination of several components including quantity of total phenolics, colouring pigments and minerals and type of phenolic compounds (Sharma et al 2010). The a values (redness) of DHC and DHCP (5.34 and 5.28) were not significantly different (p>0.05).…”
Section: Colourmentioning
confidence: 89%
“…WAC of peanut (n=2) flour and peanut protein concentrate had 1.0 and 0.83 ml/g, respectively. Similarly, Sharma et al (2010) reported that the oil absorption capacity of protein preparations absorbed more than twice own weight, ranging from 2.8 (macadamia) to 7 (soybean) g of oil/g of protein and hazelnut protein exhibited fat absorption capacity of~3 g/g of protein.…”
Section: Water Absorption Capacity (Wac) and Fat Absorption Capacity mentioning
confidence: 94%
See 3 more Smart Citations